Global and regional tree species diversity. (5th March 2018) - Qian, Hong; Deng, Tao; Sun, Hang
Abstract: Aims: Understanding tree species richness at a global scale and the origin and maintenance of patterns of tree species richness across the world is crucial to preserving tree species diversity. The recently published global tree database (i.e. GlobalTreeSearch) is the only source with tree lists at both global and national scales. However, our review and assessment show that many species included in GlobalTreeSearch are not tree species. In addition, several thousands of tree species in the botanical literature have not been included in GlobalTreeSearch. The exact number of tree species in the world remains unknown. This study aims to correct errors with GlobalTreeSearch and to estimate the number of tree species in the world based on a large number of regional floras. Methods: We standardized nomenclature and spellings of the species names according to The Plant List. We used 62 floristic sources, along with plant growth form and height, to assess the GlobalTreeSearch species checklist and to determine the degree to which GlobalTreeSearch incorrectly treated non-tree species as tree species. Important Findings: Based on our review on 60.8% of the species in the GlobalTreeSearch database and the number of additional tree species that we have found from 62 continental, national, regional and local floristic sources, we found that about 8.7% of the species included in GlobalTreeSearch are not tree species (they are herbs, shrubs or vines). We estimate that there would be about 61 000 tree species (including approximately 5500 species that are primarily shrubs but occasionally trees) in the world.